(untitled) (Ictus, 2021)
Introduction. Stroke is a significant cause of death and disability in Latin American countries. Intravenous recombinant tissue-plasminogen activator is the standard of treatment during the first 4.5 hours since stroke onset; however, a significant proportion of patients remain untreated due to late hospital arrival. Mechanical thrombectomy (MT) revolutionised stroke care by increasing the treatment window period up to 24 hours in eligible patients. Reports from Latin American countries describing the use of MT have been published, but no systematic review approach has evaluated MT in the region. Therefore, we present a systematic review protocol to assess the availability, accessibility, effectiveness, safety, and cost-utility of MT in Latin America. Material and methods. Randomised and non-randomised trials will be identified in CINAHL, MEDLINE, Web of Science, SciELO, EMBASE, and LILACS databases. Grey literature sources and clinical trial registries will be consulted. The approval of MT in the American Stroke Association was published in 2015; thus, the study search will be limited to papers published from 2015. The literature search will be conducted from February 1st, 2021, to March 31st, 2021. Additional search strategies will include citation tracking using Google Scholar and Web of Science and reference list check of the included articles. If necessary, authors from studies will be contacted for further data. Results. The results will be presented following the synthesis without meta-analysis (SWIM) guidelines. Conclusions. The results of this systematic review may be helpful for clinicians, policymakers, and stakeholders in the region.